CROWDFUNDING: THE POTENTIAL AND RISKS OF IMPLEMENTING ALTERNATIVE FUNDING MARKET IN THE CONTEXT OF THE CONTOURS OF THE GLOBAL FINANCIAL CRISIS - A. A. Grahov (Вестник СибАДИ, 2017)
Based on the performance of the macro characteristics of the economy in the country and comparing the risks of development of the economy and the introduction of crowdfunding, the article justifies the search for alternative ways of funding market through an analysis of the current state of the Russian economy; the ratio of the reasons for the slowdown in the domestic economy; changes in the structure of GDP growth of Russia, government measures to stimulate and risks of the Russian economy. Alternative financial market is represented by progressive foreign crowdfunding platforms and structure of the Russian market of crowdfunding turnover; presented and defined objectives, the development of the economy, criteria of classification and the boundaries of the risks of alternative financing, the dynamics of its development.